Reinstating plasticity and memory in a tauopathy mouse model with an acetyltransferase activator. Issue 11 (1st October 2018) - Chatterjee, Snehajyoti; Cassel, Raphaelle; Schneider‐Anthony, Anne; Merienne, Karine; Cosquer, Brigitte; Tzeplaeff, Laura; Halder Sinha, Sarmistha; Kumar, Manoj; Chaturbedy, Piyush; Eswaramoorthy, Muthusamy; Le Gras, Stéphanie; Keime, Céline; et al.
Abstract: Chromatin acetylation, a critical regulator of synaptic plasticity and memory processes, is thought to be altered in neurodegenerative diseases. Here, we demonstrate that spatial memory and plasticity (LTD, dendritic spine formation) deficits can be restored in a mouse model of tauopathy following treatment with CSP‐TTK21, a small‐molecule activator of CBP/p300 histone acetyltransferases (HAT). At the transcriptional level, CSP‐TTK21 re‐established half of the hippocampal transcriptome in learning mice, likely through increased expression of neuronal activity genes and memory enhancers. At the epigenomic level, the hippocampus of tauopathic mice showed a significant decrease in H2B but not H3K27 acetylation levels, both marks co‐localizing at TSS and CBP enhancers. Importantly, CSP‐TTK21 treatment increased H2B acetylation levels at decreased peaks, CBP enhancers, and TSS, including genes associated with plasticity and neuronal functions, overall providing a 95% rescue of the H2B acetylome in tauopathic mice. This study is the first to provide in vivo proof‐of‐concept evidence that CBP/p300 HAT activation efficiently reverses epigenetic, transcriptional, synaptic plasticity, and behavioral deficits associated with Alzheimer's disease lesions in mice. Synopsis: Epigenetic dysfunctions related to H2B histone acetylation were shown in the hippocampus of a mouse model of Alzheimer's disease. A therapeutic strategy aimed at activating CBP/p300 acetyltransferase revealed efficient at rescuing neuronal activity, plasticity and memory in these mice. Alzheimer‐related tau pathology is associated with epigenetic dysfunctions. A balanced H2Bac epigenomic landscape is maintained by CBP/HAT activity and important for hippocampus‐dependent learning and memory. A new therapeutic strategy to restore memory in cognitive diseases can be achieved by pharmacological activation of CBP/p300 acetyltransferases with CSP‐TTK21. Abstract : Epigenetic dysfunctions related to H2B histone acetylation were shown in the hippocampus of a mouse model of Alzheimer's disease. A therapeutic strategy aimed at activating CBP/p300 acetyltransferase revealed efficient at rescuing neuronal activity, plasticity and memory in these mice.